2014
DOI: 10.3390/ijms150915173
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Promotes KLF5 Proteasome Degradation through Downregulating YAP/TAZ in Bladder Cancer Cells

Abstract: KLF5 (Krüppel-like factor 5) plays critical roles in normal and cancer cell proliferation through modulating cell cycle progression. In this study, we demonstrated that curcumin targeted KLF5 by promoting its proteasome degradation, but not by inhibiting its transcription in bladder cancer cells. We also demonstrated that lentivirus-based knockdown of KLF5 inhibited cancer cell growth, while over-expression of a Flag-tagged KLF5 could partially reverse the effects of curcumin on cell growth and cyclin D1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 32 publications
2
72
0
Order By: Relevance
“…It is the main curcuminoid found in the spice turmeric, a plant alkaloid obtained from ground rhizome of the perennial herb Curcuma longa (13). According to investigations, curcumin has multiple biofunctional activities including anti-inflammatory, antioxidant, anti-cancer, anti-diabetes and chemo preventative activities (14)(15)(16)(17)(18).…”
Section: Nakhostinmentioning
confidence: 99%
“…It is the main curcuminoid found in the spice turmeric, a plant alkaloid obtained from ground rhizome of the perennial herb Curcuma longa (13). According to investigations, curcumin has multiple biofunctional activities including anti-inflammatory, antioxidant, anti-cancer, anti-diabetes and chemo preventative activities (14)(15)(16)(17)(18).…”
Section: Nakhostinmentioning
confidence: 99%
“…It has been reported that KLF5 has a role in different cell processes, including in cell proliferation, cell cycle progression and apoptosis (9)(10)(11). Previous studies have demonstrated that KLF5 acts as an oncogene in different cancer cells, and is a potential tumor suppressor in prostate cancer cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed using a previously described method (11). A total of 2x10 6 LNCaP cells were washed once with cold PBS and lysed in radioimmunoprecipitation assay buffer (50 mM Tris pH 8.0, 150 mM NaCl, 0.1% SDS, 1% NP-40, and 0.5% sodium deoxycholate) containing 1% protease inhibitor cocktail and 1 mM phenylmethanesulfonyl fluoride (Sigma-Aldrich; Merck KGaA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations